Pseudouridine-Modifying Enzymes SapB and SapH Control Entry into the Pseudouridimycin Biosynthetic Pathway - Artukka Erika; Schnell Robert; Palmu Kaisa; Rosenqvist Petja; Szodorai Edit; Niemi Jarmo; Virta Pasi; Schneider Gunter; Metsä-Ketelä Mikko (AMER CHEMICAL SOC, 2025)
Pseudouridimycin is a microbial C-nucleoside natural product that specifically inhibits bacterial RNA polymerases by binding to the active site and competing with uridine triphosphate for the nucleoside triphosphate (NTP) addition site. Pseudouridimycin consists of 5 '-aminopseudouridine and formamidinylated, N-hydroxylated Gly-Gln dipeptide moieties to allow Watson-Crick base pairing and to mimic protein-ligand interactions of the triphosphates of NTP, respectively. The metabolic pathway of pseudouridimycin has been studied in Streptomyces species, but no biosynthetic steps have been characterized biochemically. Here, we show that the flavin-dependent oxidase SapB functions as a gate-keeper enzyme selecting pseudouridine (KM = 34 mu M) over uridine (KM = 901 mu M) in the formation of pseudouridine aldehyde. The pyridoxal phosphate (PLP)-dependent SapH catalyzes transamination, resulting in 5 '-aminopseudouridine with a preference for arginine, methionine, or phenylalanine as cosubstrates as amino group donors. The binary structure of SapH in complex with pyridoxamine-5 '-phosphate and site-directed mutagenesis identified Lys289 and Trp32 as key residues for catalysis and substrate binding, respectively. The related C-nucleoside oxazinomycin was accepted as a substrate by SapB with moderate affinity (KM = 181 mu M) and was further converted by SapH, which opens possibilities for metabolic engineering to generate hybrid C-nucleoside pseudouridimycin analogues in Streptomyces.